Everyday life on the medieval Silk Road: VDSRS excavations at Arpa, Armenia - Babajanyan, Astghik; Franklin, Kathryn (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
The contemporary term ‘Silk Road’ refers to multiple centuries of movement, exchange and mutual development that tied together the cities, towns and route networks of Eurasia. During the high and late medieval periods (12th -15th centuries AD), the routes of the ‘Silk Road’ linked cities in China to the Mediterranean, passing through Central Asia and the Caucasus. The phenomenon of the medieval Silk Road is important for historical narratives within the Republic of Armenia: longstanding models of the rise of cities and kingdoms in Armenia argue that settlements such as Dvin and Ani, were linked into networks of trade between East and West. Medieval material culture within Armenia in many ways demonstrates the intersection of multiple cultures: in architecture, ceramics, glass, numismatics and other spheres. Within the medieval Silk Road networks of the south Caucasus, the region of Vayots Dzor is centrally located, and in the medieval period served as a junction point in north-south and east-west routes of travel (Figure 1).